Transformation geometry in eleventh grade using digital manipulative batik activities - Sahara, Sani; Dolk, Maarten; Hendriyanto, Agus; Kusmayadi, Tri Atmojo; Fitriana, Laila (Universitas Sriwijaya in collaboration with Indonesian Mathematical Society (IndoMS), 2024)
Learning Transformation Geometry (TG) needs a more informal approach to concern situational problems. This study aims to develop actionable knowledge of TG in the form of design related to context and yet general enough to use digital manipulative activities in new situations. We propose such knowledge in the form of conjectured Local Instructional Theory (LIT) in the framework of design research methodological framework. The designed learning activities were based on Realistic Mathematics Education (RME) principles and used batik as the context and van Hiele’s mode of geometric thought. In addition, the CorelDraw software is used as a tool to transform batik-making activities into a digital manipulative environment. The design consists of a pre-assessment and four learning activities. The data were analyzed retrospectively in accordance with the HLT. The analysis of the data described above and the justification of the processes during the teaching experiment indicate a compelling trajectory for students learning transformation geometry for this specific context and the prospect for future studies.